KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH MATEMATIS SISWA : DAMPAK STRATEGI WANKAT-OREOVOCZ - Ningrum, Della Tri Aditiya; Pahrudin, Agus; Andriani, Siska (Jurnal Karya Pendidikan Matematika, 2021)
This research was conducted with the aim of analyzing the results of the application of the Wankat-oreovocz strategy on students' ability to understand concepts and solve mathematical problems. This study uses a quasi-experimental research type. The sample in this study were students of class XIA and XIB MA Darun Nasyi'in, East Lampung.The sample in this study were students of class XIA and XIB MA Darun Nasyi'in, East Lampung. The sampling technique used was cluster random sampling. The research data collection techniques were in the form of tests and documentation. The data analysis technique used was the normality and homogeneity test.Testing the hypothesis in this study using the Multivariate Analysis of Variance (Manova) test.The results of the study and the Manova test calculation, concluded that there was an effect of the wankat-oreovocz strategy on the ability tounderstand concepts. There is an effect of the wankat-oreovocz strategy on problem solving abilities. There is an effect of the wankat-oreovocz strategy on students' ability to understand concepts and solve mathematical problems.